Pengaruh Boikot Besar-besaran Produk Amerika terhadap Peningkatan Jumlah Pengangguran di Indonesia - Marbun, Daniel Anugrah; Sinaga, Edo Immanuel; Sianturi, Felix Raphael; Zulkarnain, T. Faiz Mubarak; Hazira, Rizki; Sarita, Nadia; Putri, Nirwana Dewantari Yani (Polyscopia, 2024)
This research aims to analyze the impact of a large-scale boycott of United States products on the increase in unemployment in Indonesia. The boycott was driven by political tensions and controversial trade policies. Using quantitative analysis with secondary data from the Central Statistics Agency (BPS), company financial reports, and labor market surveys, the research shows a significant impact on sectors dependent on United States products and investments. Declines in sales and production in affected companies led to layoffs and higher unemployment rates. The impact was more pronounced in regions with concentrated industries related to American products. The study concludes that the boycott contributed to higher unemployment in Indonesia, with varying impacts across sectors and regions. These findings suggest important implications for policymakers in mitigating the economic effects of boycotts and highlight the need for economic diversification to reduce reliance on specific imported products.